Les formes contemporaines de l'antimaçonnisme - Rousse-Lacordaire, Jérôme (PHR series, 2019)
Anti-Masonic discourse is enjoying a spectacular resurgence, not only in Europe, but also in the Muslim world, sub-Saharan Africa and Latin America. This book offers a new assessment of the issue, in the light of the most recent developments.